2017
DOI: 10.1038/mi.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with a heat-killed probiotic modulates monocyte chemoattractant protein-1 and reduces the pathogenicity of influenza and enterovirus 71 infections

Abstract: It has been proposed that inactivated probiotics may modulate the host immune system and contribute to mitigation of viral infections. This study demonstrated that administration of heat-killed Enterococcus faecalis, a widely used probiotic, can protect host animals against viral infections. The influenza-mediated morbidity and lung inflammation in E. faecalis-treated mice decreased significantly compared with those of the control mice. Furthermore, we found that the protection is associated with production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Our studies have showed that the immunomodulatory effect of some nasally administered immunobiotics persisted for at least 15 days (Villena et al, unpublished results). Other studies have also reported short-term protection after nasal treatment with different immunobiotic strains (43). Interestingly, Garcia-Crespo et al (52) found that adult mice primed nasally with L. plantarum NCIMB 8826 or Lactobacillus reuteri F275 were completely protected against lethal PVM infection and that protection persisted for at least 5 months after the initial priming.…”
Section: Beneficial Effects Of Immunobiotics On Ifv Infectionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our studies have showed that the immunomodulatory effect of some nasally administered immunobiotics persisted for at least 15 days (Villena et al, unpublished results). Other studies have also reported short-term protection after nasal treatment with different immunobiotic strains (43). Interestingly, Garcia-Crespo et al (52) found that adult mice primed nasally with L. plantarum NCIMB 8826 or Lactobacillus reuteri F275 were completely protected against lethal PVM infection and that protection persisted for at least 5 months after the initial priming.…”
Section: Beneficial Effects Of Immunobiotics On Ifv Infectionmentioning
confidence: 93%
“…Chen et al (43) also investigated the ability of orally administered Enterococcus faecalis KH2 to beneficially modulate the innate immune response to influenza infection. Authors observed that KH2 strain protected C57BL/6 mice against IFV as observed by the reduced mortality, weight loss, and lung viral titers.…”
Section: Beneficial Effects Of Immunobiotics On Ifv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been assumed that probiotic bacteria need to be alive to confer health benefits on the body when administered in an adequate amount; however, there have been concerns that live bacteria could cause unwanted side effects. To avoid these unwanted side effects, heat- or UV-inactivated bacteria have been assessed as a substitute, and their beneficial effects on the body were found to be similar to the benefits of live bacteria 6 , 18 , 19 . In addition, heat- or UV-inactivated bacteria possess several advantages such as safe, stable and easy handling compared with live bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies reported that heat-killed probiotics have a similar level of immunomodulatory abilities as live probiotics, despite a lack of viability. In case of Enterococcus faecalis and L. plantarum 06CC2, administration of heat-treated LAB on mice before influenza virus infection reduced morbidity and alleviated symptoms (Takeda et al, 2011;Chen et al, 2017b). Therefore, by using heattreated probiotics as an additive, it can be easier to increase immunomodulatory properties of yogurt with prolonged shelf life and easier storage properties.…”
Section: Discussionmentioning
confidence: 99%